Multiple solutions of mixed convective MHD casson fluid flow in a channel - Raza, Jawad; Mohd Rohni, Azizah; Omar, Zurni (Hindawi, 2016)
A numerical investigation is made to determine the occurrence of the multiple solutions of MHD Casson fluid in a porous channel. Governing partial differential equation of the proposed problem converted into nonlinear ordinary differential equations by using similarity transformation. Numerical technique known as shooting method is used to investigate the existence of the multiple solutions for the variations of different parameters. Effects of physical parameters on velocity profile, temperature, concentration, and skin friction are presented in pictorial and tabulation representation.